Educating Digital Curators: Challenges and Opportunities - Peter Botticelli; Bruce Fulton; Richard Pearce-Moses; Christine Szuter; Pete Watters (International Journal of Digital Curation, 2011)
This paper describes a number of critical challenges faced by digital curation educators and suggests how the choices we make in building educational programs may impact the development of curation as a professional discipline. We focus on curriculum and program building as key steps in defining the educational needs of curators, and we argue for greater collaboration among educators, researchers and practitioners in the field, as a way to speed the emergence of curation as a discipline and to foster the integration of curation programs within libraries and archives.